(untitled) (SCIÉNDO INGENIUM, 2023)
This research aims to compare two treatments for detoxification of cyanide mine tailings using hydrogen peroxide, the first one with a concentration of 50% and the second one with a concentration of 70%. The statistical tool ANOVA was used, together with the tukey method, to determine the differences and similarities of both treatments. The study was carried out in two trains composed of five tanks each, the treatment was randomized (DCA) for a period of 21 hours, obtaining a cyanide sample from each tank every hour. The results showed that the 70% peroxide treatment provides higher cyanide removal (<0.05 ppm), lower solvent consumption (975 kg) and lower consumption ratio (0.58 kg/m3), also, a solvent saving of 36% was obtained; the ANOVA analysis showed a significant influence between the peroxide concentration and cyanide removal, and also, that there is no relationship between the detoxification time and the final cyanide concentration for both treatments. In sum, the 70% peroxide treatment allows an effective cyanide removal, complying with the maximum permissible limits for its discharge, in accordance with the Peruvian legislation in force.